Accurate holographic cytometry using three-dimensional hydrodynamic focusing. (1st February 2023) - Patel, Yogesh M; Malik, Ritika; Khare, Kedar; Bahga, Supreet Singh
Abstract: We present a microfluidic holographic cytometry technique using three-dimensional (3D) hydrodynamic focusing for accurate visualization, classification, and quantification of the cells and particles from a mixture. Our approach uses high-resolution, single-shot digital holographic microscopy to image moving cells and particles in a specially-designed microfluidic device that orders the cells and particles in a single file close to the bottom wall of the channel. Our 3D-focusing microfluidic device allows high-magnification holographic imaging without the need for computationally-expensive numerical refocusing used by the existing holographic cytometry techniques. Our microfluidic device also prevents the clustering of cells and can be fabricated at a low-cost using micromilling. To demonstrate the efficacy of our method, we consider a challenging case of classification from a mixture of unstained red blood cells and polystyrene particles, which are otherwise indistinguishable in brightfield and phase-contrast microscopy. Through experiments with cell-particle mixtures with varying proportions, we show that our holographic cytometry technique can precisely count and classify the cells and particles based on their reconstructed phase values. Our holographic cytometry technique has the potential for label-free classification and quantification of infected cells for applications such as disease diagnostics, cancer research, and genomics.